How to Rise to Texts? On Joanna Pollakówna, an Essayist - Szulc-Woźniak, Agata (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The paper focuses on the essayistic output of Joanna Pollakówna, a poet and a historian of art, an author of several books of sketches devoted to European painting. It draws attention to the necessity of reading her poetry and essays – which are inseparable and illuminate one another – in a parallel way. The first part of the article analyses the way of treating art typical of Pollakówna: the experience of reception which reveals the following of the illumination, the awareness of significance, and mystery. The paper shows that the poet’s strategy towards the mystery of beauty consists in launching the empathic imagination capable of capturing the fleeting experience which seems to escape. The response to painting – which goes beyond the level of interpretation and chooses ‘adding’ rather than cataloguing meanings – is treated, after Didi-Huberman, as “capturing through the visible”, which leads to “producing and transforming”. The second part of the article is devoted to selected essays which manifest the transition from the intuition of mystery to the in-depth and creative answer of imagination: imagination following not only the work of art, but also the artist, the interesting relationship between them. References are made, for instance, to the private archive of the poet and her notes from art galleries. The reception of Pollakówna’s work is discussed in the conclusion of the paper. Quoting the voices of critics and the private correspondence of the poet with editors (which remains unpublished), one may argue that the essayistic method of the poet has been both acclaimed and not comprehended.